A Rare Ectopic Ovary Mimicking Colon Sigmoideum Mesenchymoma Presenting as an Intestinal Mesenchymoma - Pan, Jiyong; Wang, Shuang; Wang, Hai; Fan, Zhe (Frontiers in Oncology, 2019)
Ectopic ovaries are a rare occurrence. A 33-year-old woman presented to our unit for evaluation of a 2-year history of sporadic abdominal pain that was becoming sharp and frequent. Computed tomography suggested a gastrointestinal tract mesenchymoma. An abdominal laparotomy was performed and the tumor was excised for pathologic evaluation. A rapid frozen section pathologic examination showed a solitary fibrous tumor. The final pathology report was an ectopic ovary with corpora lutea bleeding. Ectopic ovaries are benign and the present case is the first report involving an ectopic ovary mimicking a gastrointestinal stromal tumor (GIST). The patient recovered well after surgery. Maldevelopment of the genital tract can lead to ectopic ovaries and surgery is a good management choice. The present case provides a possible differential diagnosis for GISTs.